2013
DOI: 10.17269/cjph.104.3721
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Relative Timeliness of Ontario’s Syndromic Surveillance Systems for Early Detection of the 2009 Influenza H1N1 Pandemic Waves

Abstract: OBJECTIVES:Building on previous research noting variations in the operation and perceived utility of syndromic surveillance systems in Ontario, the timeliness of these different syndromic systems for detecting the onset of both 2009 H1N1 pandemic (A(H1N1)pdm09) waves relative to laboratory testing data was assessed using a standardized analytic algorithm. METHODS:Syndromic data, specifically local emergency department (ED) visit and school absenteeism data, as well as provincial Telehealth (telephone helpline)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…Our findings confirm previous evaluations that found moderate to high correlation and timeliness of TT data compared with ILI surveillance and international health agency–reported or laboratory-confirmed cases of influenza. 4,7,8,12,13 In 1 study, national triage call data from 17 states had a median correlation (using the Pearson correlation test) of 0.65 between call data and CDC viral isolate data, 4 whereas the correlation of VA-TT calls with CDC viral isolate data in our study was 0.82. Another study from Ireland found correlations between influenza-related TT calls and national ILI rates as high as 0.90.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Our findings confirm previous evaluations that found moderate to high correlation and timeliness of TT data compared with ILI surveillance and international health agency–reported or laboratory-confirmed cases of influenza. 4,7,8,12,13 In 1 study, national triage call data from 17 states had a median correlation (using the Pearson correlation test) of 0.65 between call data and CDC viral isolate data, 4 whereas the correlation of VA-TT calls with CDC viral isolate data in our study was 0.82. Another study from Ireland found correlations between influenza-related TT calls and national ILI rates as high as 0.90.…”
Section: Discussionmentioning
confidence: 45%
“…With early detection of influenza a priority, nontraditional data sources (ie, absenteeism, over-the-counter drug sales, internet searches, and telephone triage [TT]) are being evaluated as additional sources of surveillance information. [2][3][4][5][6][7][8][9][10][11][12][13][14] TT is a method whereby a medical professional, usually a registered nurse, speaks with a patient or caregiver by telephone to assess the patient's symptoms or health concerns and offer medical advice. TT is an interactive process between the TT professional and the client, with the goal of directing the caller to the appropriate level of care or service in a safe and timely manner.…”
mentioning
confidence: 99%
“…However, despite the existing wealth of literature, and the importance of early detection (item (d) above) for disease control, the authors have been unable to find any previous publication which deals with the quantitative evaluation of this form of surveillance, except for syndromic surveillance (see e.g. (Bedubourg & Strat, 2016; Chu et al., 2013; Faverjon, Vial, Andersson, Lecollinet, & Leblond, 2017)) and application of methodologies originally designed to demonstrate freedom (Welby et al., 2017).…”
Section: The Purposes Of Surveillancementioning
confidence: 99%
“…Examples of public health process research (rather than data combining/sharing) were found across EDSyS in Canada [127][128][129]. Collaborative working across international borders was identified less often.…”
Section: Information For Public Health Actionmentioning
confidence: 99%